(untitled) (Biological Sciences - PJSIR, 1999)
The seeds of Citrullus colocynthis were germinated inthe dark at 30°C andthe variations in the lipidclass and fatty acid composition of primary roots andthe respective cotyledons at 5 mmto 30 mm root length were studied. During germination therelativeamountsoftriacylglycerols decreasedwhilefreefattyacids increasedcontinuously insignifi- cant amounts. Polar lipidsalsoincreasedwiththeincreaseofrootlength.Saturatedfatty acidsincreased (exceptlauric acid) whereas the unsaturated fatty acids decreased graduaJlyduring thecourse of germination.